Comparative Characterization of Diphenolases from Two Mulberry Fruits (Morus alba L. and Morus nigra L.) - COLAK, A.; KOLCUOGLU, Y.; FAIZ, O.; OZEN, A.; DINCER, B. (Asian Journal of Chemistry, 2010)
Fruits of two mulberry cultivars (Morus alba L. and Morus nigra L.) were investigated for their polyphenol oxidase potentials. Native electrophoresis of the crude extracts prepared from the cultivars stained with L-DOPA showed similar patterns with Rf values of 0.15 (one major band), 0.42 and 0.54 (two minor bands), respectively. The crude extracts from each mulberry cultivars (Morus alba L. and Morus nigra L.) were highly active against 3-(3,4-dihydroxyphenyl)propionic acid at acidic and neutral pH values and possessed temperature optima of 40 and 20ºC, respectively. pH-stability profiles showed that crude enzymes were extremely stable at both their optimum pH and alkaline pH values. The diphenolase activities from the two mulberry cultivars were very sensitive to ascorbic acid and metabisulfite with IC50 values lower than 1 mM. Moreover, both inhibitors exhibited complete inhibition of 3-(3,4-dihydroxyphenyl)propionic acid oxidation at 1 mM and 2 mM concentrations, respectively. 5 mM sodium dodecyl sulfate is required for the fully active diphenolase from Morus nigra L. It can be concluded from the present study that the crude enzymes prepared from the ripe mulberry fruits of two cultivars possess diphenolase activities sharing similar functional properties.